2021
DOI: 10.3390/su13095221
|View full text |Cite
|
Sign up to set email alerts
|

What’s the Name of the Game? The Impact of eHealth on Productive Interactions in Chronic Care Management

Abstract: Chronic care management is dependent on productive interactions between patients and healthcare professionals. Digital health technologies (eHealth) open up new possibilities for improving the quality of care, but there is a limited understanding of what productive interactions entail. This study explores characteristics of productive interactions to support self-care and healthcare in the context of eHealth use in diabetes care. We collected qualitative data based on interviews with nurses and responses to op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…They shared responsibility for monitoring, which implied a mutual dependency. The shift from traditional care to HTH-supported self-management implicitly implies that tasks are shared to a higher extent, which also implies that the distinction between HCP and patient responsibilities gets blurred as these become more intertwined, similar to what has been reported in previous studies [ 45 47 ]. This interaction can contribute to complexity.…”
Section: Discussionsupporting
confidence: 55%
“…They shared responsibility for monitoring, which implied a mutual dependency. The shift from traditional care to HTH-supported self-management implicitly implies that tasks are shared to a higher extent, which also implies that the distinction between HCP and patient responsibilities gets blurred as these become more intertwined, similar to what has been reported in previous studies [ 45 47 ]. This interaction can contribute to complexity.…”
Section: Discussionsupporting
confidence: 55%
“…One of these studies highlighted that health care professionals may need to communicate their personal boundaries to patients; for example, they would only check messages on certain weekdays [ 56 ]. However, these kinds of social interaction norms have rarely been made explicit in studies where asynchronous interactions were not structured or constrained, which could lead to a blurring of the boundaries that define the contents, extents, and times of interactions [ 67 , 68 ]. The ethical implications of digital patient-professional communication can be complex and require organizational guidelines to promote good practices in the use of digital communication [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Role clarity reflects the patients' perceptions of the boundaries between self-care and healthcare. The possibility of sharing tasks and roles between actors in the co-care system as well as new ways of interacting with each other (e.g., through e-health services or new models of care) can also lead to increasingly blurred boundaries between self-care and healthcare (7). Research has shown that patients may lack clarity about their role in collaborative care models where healthcare professionals, patients, and families work together, which may be linked to insufficient guidance about how to distribute roles (19).…”
Section: Discussionmentioning
confidence: 99%
“…Self-care of chronic conditions involves behaviors to maintain or improve physical and emotional stability (i.e., self-care maintenance), monitoring changes in signs and symptoms (i.e., self-care monitoring), and responding to signs and symptoms when they occur (i.e., self-care management) (6). The continuously rising availability and adoption of digital health technologies to support individuals in their self-care activities and communication within healthcare further blurs the boundaries between self-care and healthcare (7). For example, technology can enable individuals to take on activities traditionally performed by healthcare professionals, such as performing and monitoring blood pressure measurements (8), thereby enabling timely interventions.…”
Section: Introductionmentioning
confidence: 99%